Deep sea without limits—four new closely related species of Emertonia Wilson, 1932 (Copepoda: Harpacticoida: Paramesochridae) show characters with a world-wide distribution - Mathiske, Annabel; Thistle, David; Gheerardyn, Hendrik; Veit-Köhler, Gritta (Zootaxa, 2021)
The large-scale dispersal of deep-sea harpacticoid copepods is an increasing focus for ecological studies. A fundamental prerequisite for monitoring and explaining their geographical distribution is precise descriptions of their morphology. Four new, closely related species of the family Paramesochridae (Copepoda, Harpacticoida) were found in the deep sea of the Pacific (San Diego Trough and off Chile), the Atlantic Ocean (Porcupine Abyssal Plain and Angola Basin), and the Atlantic and Indian Ocean sectors of the Southern Ocean (Weddell Sea and off Crozet Island). The discovery of Emertonia berndi sp. nov., E. hessleri sp. nov., E. ilse sp. nov., and E. serrata sp. nov. increases the number of known deep-sea species in this genus to ten. The new species are placed in Emertonia Wilson, 1932 because of their one-segmented endopods on the second and third swimming legs. The presence of a two-segmented endopod on the fourth swimming leg allocates them to the “andeep-group” within this genus. The four species can be distinguished from their congeners by the strongly serrated spines on the exopods of their swimming legs and an outwardly directed flexible seta on the exopod of the fifth leg. It is conveivable that these two specific characters evolved only once in the genus Emertonia. Their apparently cosmopolitan distribution covers thousands of kilometres and spans all major oceans. This biogeographical pattern may be explained by resuspension events followed by passive transport by benthic currents. Discrepancies in their dispersal ranges may be a result of changing geological and oceanographic boundaries.